Perlindungan Hukum Bagi Kreditur Terhadap Kredit Macet Dengan Jaminan Hak Tanggungan - Tami Rusli (Universitas Bandar Lampung (UBL), 2016)
Event of default committed by the debtor in the credit agreement would be detrimental to the creditors, so we need a rule of law in the implementation of the imposition of Mortgage as collateral contained in a credit agreement. The problem in this research is how the legal protection against creditors in the bank credit agreement by UUHT ?. The approach used in this research is normative juridical and empirical approach. Data collected by literature study and field studies. Analysis of qualitative data. Results of research legal protection against creditors in the bank credit agreement by UUHT is the form of protection concerning the clarity of the administration, a form of protection as outlined in the principles encumbrance, a form of protection that gives legal certainty to creditors in terms of sales object security rights through the implementation of sales below hand. advice delivered is supervision and guidance made by the bank should be increased, without any intention to interfere in the affairs of